Sporadic E ionization layers observed with radar imaging and ionospheric modification. Issue 20 (18th October 2014) - Hysell, D. L.; Munk, J.; McCarrick, M.
Abstract Sporadic E ionization layers have been observed in the daytime subauroral ionospheric E layer by a 30 MHz radar in Alaska. The radar detects coherent backscatter from meter‐scale field‐aligned plasma density irregularities. The irregularities were generated by ionospheric modification—by the emission of strong HF electromagnetic waves directly beneath the layers—making the layers visible to the radar. Aperture‐synthesis methods are used to generate imagery of the layers from the radar data. The layers are patchy, with patches organized along fronts spaced by tens of kilometers and propagating slowly toward the southwest. Similar, naturally occurring layers are commonly observed at middle latitudes at night in the absence of ionospheric modification. That the patchy layers can be found at high magnetic latitudes during the day argues that they are most likely produced through the interaction of the ionospheric layer with neutral atmospheric waves and instabilities. Attenuation of the radar echoes when the HF emission frequency exceeded the third harmonic of the electron gyrofrequency was observed and is discussed.